Media Pembelajaran Pengenalan Alat Musik Tradisional Batak Toba Dengan Adobe Flash CS3 Di SD Kesatria Medan - Heppy Anggraeni Gulo; R Ramli; Yuyun Dwi Lestari (LPPM STIKOM Tunas Bangsa, 2022)
The world of education today has also implemented or used technology as a tool in the teaching and learning process. At this time, the teaching and learning process, especially in cultural arts subjects related to the introduction of traditional Batak Toba musical instruments at SD Kesatria Medan still has several shortcomings, one of which is, the way of delivering information / lessons related to the introduction of Batak Toba musical instruments is still done by teachers in SD Kesatria Medan is to read books related to Batak Toba musical instruments, therefore in this study, the author wants to build a learning media related to the introduction of Batak Toba musical instruments using Adobe Flash CS3, in order to attract students' interest in learning the introduction of musical instruments Batak Toba